Sharing regulatory data as tools for strengthening health systems in the Region of the Americas - Varley Dias Sousa; Pedro I. Ramalho; Dâmaris Silveira
ABSTRACT Regulatory transparency is an imperative characteristic of a reliable National Regulatory Authority. In the region of the Americas, the process of building an open government is still fragile and fragmented across various Health Regulatory Agencies (HRAs) and Regional Reference Authorities (RRAs). This study assessed the transparency status of RRAs, focusing on various medicine life-cycle documents (the Medicine Dossier, Clinical Trial Report, and Inspection Report) as tools for strengthening health systems. Based on a narrative (nonsystematic) review of RRA regulatory transparency, transparency status was classified as one of two types: public disclosure of information (intra-agency data) and data- and work-sharing (inter-agency data). The risks/benefits of public disclosure of medicine-related information were assessed, taking into account 1) the involvement and roles of multiple stakeholders (health care professionals, regulators, industry, community, and academics) and 2) the protection of commercial and personal confidential data. Inter-agency data- and work-sharing was evaluated in the context of harmonization and cooperation projects that focus on regulatory convergence. Technical and practical steps for establishing an openness directive for the pharmaceutical regulatory environment are proposed to improve and strengthen health systems in the Americas. Addressing these challenges requires leadership from entities such as the Pan American Health Organization to steer and support collaborative regional alliances that advance the development and establishment of a trustworthy regulatory environment and a sustainable public health system in the Americas, using international successful initiatives as reference and taking into account the domestic characteristics and experiences of each individual country.